PENERAPAN MANUAL BOOK BERDASARKAN VOLUME 2 ICD-10 TENTANG KODING PENYAKIT DI PUSKESMAS KENDALSARI - ., Pratiwi; Kunta, Ittaqillah Haitsuma (DINAMIKA DOTCOM, 2018)
One of the medical record activities in puskesmas is the diagnosis of disease, according to ICD-10. Coder at Puskesmas Kendalsari in establishing the disease diagnosis code has not implemented the coding steps, according to volume 2 ICD-10. This is one of the causes of inaccuracies of disease diagnostic codes. This study aims to implement a manual book made in accordance with volume 2 ICD-10, about the procedure of giving the disease code. The research instruments are checklist, ICD-10 and interview guidelines. Population is an outpatient medical record file at Puskesmas Kendalsari. The number of samples is 50 records of medical records. The study design is the pre-experiment One Group Pretest Postest by measuring the percentage of accuracy of diagnosis code of disease diagnosis before and after manual book implementation. The results showed the percentage of accuracy of disease diagnosis code before manual book implementation by 42%; While after the implementation of the manual book by 82%. Statistic test with Independent Z Test obtained Sig value. Less than 0.05 ie 0,000 which means Ho is rejected, meaning there is a difference in the proportion of the accuracy of the diagnosis of disease diagnosis before and after the implementation of the manual book. We recommend that the manual book can be used as a guide in determining the diagnostic code of the disease in Puskesmas Kendalsari. Keywords: diagnostic code, manual book